The Law on Climate Change and Waste Management from the Perspective of Greenhouse Gas Emissions Mitigation - Huan, Tran Linh (VNU Journal of Science: Legal Studies; Vol 39 No 3DO - 10.25073/2588-1167/vnuls.4463, 2023)
Climate change and waste management have always been closely linked and impactful to each other. Looking at the goal of mitigating greenhouse gas emissions will show the requirements for adjusting the waste management methods, processes, technologies, etc.. Therefore, this article focuses on analyzing the aspects of waste management related to climate change, and identifying solutions to promote the goal of reducing greenhouse gas emissions in waste management in Vietnam today